Responsiveness of the Tampa Scale of Kinesiophobia in Italian subjects with chronic low back pain undergoing motor and cognitive rehabilitation - Monticone, Marco; Ambrosini, Emilia; Rocca, Barbara; Foti, Calogero; Ferrante, Simona (European spine journal, 2016)
Purpose The Tampa Scale of Kinesiophobia (TSK) is a commonly used measure for the assessment of kinesiophobia related to spinal diseases. The Italian version showed satisfactory psychometric properties, but its responsiveness has not yet been evaluated. This observational study is aimed at evaluating the responsiveness and minimal important changes (MICs) for the TSK in subjects with chronic low back pain. Methods At the beginning and end of an 8-week multidisciplinary rehabilitation programme, 205 patients completed the TSK. After the programme, patients also completed the global perceived effect (GPE) scale, which was divided to produce a dichotomous outcome. Responsiveness was calculated by distribution [effect size (ES); standardised response mean (SRM)] and anchor-based methods [receiver-operating characteristics (ROC) curves; correlations between change scores of the TSK and GPE]. ROC curves were also used to compute the best cut-off levels between subjects with a “good” or “poor” outcome (MICs). Results The ES and the SRM were 1.49 and 1.36, respectively. The ROC analyses revealed a MIC value (AUC; sensitivity; specificity) of 5.5 (0.996; 95; 97). To avoid any dependence on the baseline scores, the MIC value [area under the curve (AUC); sensitivity; and specificity] was computed also based on the percentage of change from the baseline and a value of 18 % (0.998; 97; 98 %) was obtained. The correlation between change scores of the TSK and GPE was high (0.871). Conclusions The TSK was sensitive in detecting clinical changes in subjects with chronic low back pain. We recommend taking the MICs provided into account when assessing patients’ improvement or planning studies in this clinical context.